Memahami Konsep, Jenis, Prinsip Serta Teori Dalam Pengeluaran Pemerintah - Putri, Elivia Pasma (CV. Kurnia Grup, 2025)
Government spending is a very important part of an economic system, namely where the government has the absolute right to participate in every economic activity, where the government not only allocates goods but also participates in managing goods and services, increasing international sales, economic stability, and encouraging accelerated economic growth. Government spending includes a number of planning, implementation, and evaluation activities in order to achieve development goals; government spending functions to provide public services, infrastructure, and social security needed to improve the welfare of the community. In each government period, spending policies are often determined based on various development priorities, ranging from education and health to infrastructure development. The research conducted by the author uses a qualitative method with a literature study approach starting from collecting, analyzing, and organizing sources from articles, books, and research, then concluding and finally presenting complete information about government spending. This research aims to understand the importance of the effectiveness and efficiency of government spending; therefore, through this article, the concept of government spending, types of government spending, principles of government spending, and expenditure theory will be discussed.